2014
DOI: 10.1002/glia.22654
|View full text |Cite
|
Sign up to set email alerts
|

What is microglia neurotoxicity (Not)?

Abstract: Microglia most likely appeared early in evolution as they are not only present in vertebrates, but are also found in nervous systems of various nonvertebrate organisms. Mammalian microglia are derived from a specific embryonic, self-renewable myeloid cell population that is throughout lifetime not replaced by peripheral myeloid cells. These phylogenic and ontogenic features suggest that microglia serve vital functions. Yet, microglia often are described as neurotoxic cells, that actively kill (healthy) neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
114
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 183 publications
2
114
0
Order By: Relevance
“…Based on this study and previous reports, we found that the observed expression of galectin‐3, rather than the differences in the time‐course of the two M1 and M2 phenotype macrophage markers after HI between the immature and the mature hippocampus, correlated with the age‐dependent effects of HI (Fernández‐López et al, 2014). However, a single M1 or M2 phenotype marker does not classify individual microglia as pro‐ or anti‐inflammatory, rather, the combined expression of multiple markers produce a continuous spectrum of functional heterogeneity (Biber et al, 2014), and more comprehensive approaches are needed to more accurately phenotype individual microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this study and previous reports, we found that the observed expression of galectin‐3, rather than the differences in the time‐course of the two M1 and M2 phenotype macrophage markers after HI between the immature and the mature hippocampus, correlated with the age‐dependent effects of HI (Fernández‐López et al, 2014). However, a single M1 or M2 phenotype marker does not classify individual microglia as pro‐ or anti‐inflammatory, rather, the combined expression of multiple markers produce a continuous spectrum of functional heterogeneity (Biber et al, 2014), and more comprehensive approaches are needed to more accurately phenotype individual microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst Cx3cr1 knockout experiments in Parkinson's disease, ALS and Alzheimer's disease models have indicated a role for CX3C signalling (Cardona et al, 2006;Lee et al, 2010;Cho et al, 2011), our experiments suggest that CX3CR1 is not essential to the microglial response in prion disease. As others have proposed, some redundancy may exist in the signalling mechanisms that regulate microglia (Biber et al, 2014), thus other molecules such as CD200/CD200R and/ or TREM2 may play an augmented role upon deletion of Cx3cr1 in prion disease models.…”
mentioning
confidence: 99%
“…During activation, microglia undergo morphological changes, proliferate, migrate and produce cytokines and chemokines in reaction to central nervous system (CNS) infection and injury. Whilst this activation has homeostatic functions, it can also be neurotoxic and contribute to disease progression (Biber et al, 2014;Ransohoff et al, 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations